RATES OF APPLICATION OF Azospirillum brasilense IN TOMATO CROP (REVISTA DE AGRICULTURA NEOTROPICAL, 2018)
The use of plant growth-promoting bacteria (PGPB) may be a promising agronomic practice to improve the growth and productivity of vegetables. The objective of this work was to evaluate the effect of inoculation of Azospirillum brasilense on plant growth and tomato fruit production. Two experiments were carried out: the first one evaluating the growth of the plants in a greenhouse and the second one evaluating the production of fruits under field conditions. The experimental design used in two experiments was the completely randomized 2 x 5 factorial scheme, with four replications. The treatments resulted from the combination of two tomato cultivars (Gaúcho Melhorado and San Marzano) and four inoculant doses (0; 2; 4; 6 e 8 mL kg-1 of seed) containing the Ab-V5 and Ab-V6 strains of A. Brasilense. The application of inoculant containing A. brasilense improved the growth and dry matter production of tomato cultivars Gaúcho Melhorado and San Marzano. The highest values of plant height, stem diameter, root length, root volume, relative chlorophyll content and dry matter of shoots and roots are obtained with the dose of 4 to 6 mL kg-1 of inoculant, allowing to infer that the maximization of plant growth and the production of tomato fruits with the application of inoculant containing Azospirillum brasilense can be obtained with the use of approximately 5.0 mL kg-1 of seeds for tomato cultivars.